Ptice gnezdilke v senožetnih sadovnjakih na Pohorju - Vogrin, Milan (Gozdarski vestnik, 2009)
On Mt. Pohorje in NE Slovenia breeding birds in 30 traditional orchards with total area of 22.4 ha were studied in 1993 and 1994. Among the most frequent trees was apple-tree which was found in all studied orchards. The most frequent breeders were Tree Sparrow Passer montanus, Goldfinch Carduelis carduelis and Greenfinch Carduelis chloris. Average breeding density was 46 pairs/10 ha. Breeding communities were also analyzed in relation to their nesting site, feeding and migratory habits. The number of species increased with the size of the traditional orchards and the number of trees.
Keywords: bird; ptice; gnezdenje; sadovnjaki; Pohorje